2019
DOI: 10.1017/s0272263119000408
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual Children’s Phonology Shows Evidence of Transfer, but Not Deceleration in Their L1

Abstract: Bilingual language development might be characterized by transfer, deceleration, and/or acceleration, the first two being relevant for the language impairment diagnosis. Studies on bilingual children’s productive phonology show evidence of transfer, but little is known about deceleration in this population. Here, we focused on phonological transfer and deceleration in L1 speech of typically developing Polish-Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…From the initial sample of 56 participants, we selected a subset of 37 participants such that they matched the migrant group as closely as possible on a set of critical measures: chronological age, age of L2 acquisition, socio-economic status (SES), language proficiency (the combined score of the LexTALE and Cambridge tasks) and self-assessed language switching behavior. The matching procedure was carried out using a brute force algorithm that we also used for a similar purpose in a previous study (Marecka et al, 2020). The groups had means within 1 SD of each matched variable (see Table 1 for the observed similarities and differences between the groups).…”
Section: Participantsmentioning
confidence: 99%
“…From the initial sample of 56 participants, we selected a subset of 37 participants such that they matched the migrant group as closely as possible on a set of critical measures: chronological age, age of L2 acquisition, socio-economic status (SES), language proficiency (the combined score of the LexTALE and Cambridge tasks) and self-assessed language switching behavior. The matching procedure was carried out using a brute force algorithm that we also used for a similar purpose in a previous study (Marecka et al, 2020). The groups had means within 1 SD of each matched variable (see Table 1 for the observed similarities and differences between the groups).…”
Section: Participantsmentioning
confidence: 99%
“…In fact, cross-linguistic interaction is not specific to adult heritage bilingualism. Utilizing the framework of early grammar interaction developed by Paradis and Genesee (1996), scholars have shown that the phonological grammars of bilingual speakers during early childhood demonstrate several characteristic features, including transfer (i.e., adoption of a property of language A into language B) (Dickinson, McCabe, Clark-Chiarelli, & Wolf, 2004;Erikson, 2016;Goldstein & Bunta, 2011;Lleó, 2018;Marecka, Wrembel, Otwinowska, Szewczyk, & Banasik-Jemielniak, 2020), deceleration (i.e., lower rate of acquisition when compared to monolinguals; Fabiano-Smith & Barlow, 2010;Kehoe, 2002;Kehoe, Lleó, & Rakow, 2004;Menke, 2018), and, to a lesser extent, acceleration (i.e., faster rate of acquisition when compared to monolinguals; Kehoe, Trujillo, & Lleó, 2001;Tamburelli, Sanoudaki, Jones, & Sowinska, 2015).…”
Section: Introductionmentioning
confidence: 99%